Peran (Cerpen) SK Pensiun Karya Ahmad Tohari dalam Pembentukan Pendidikan Karakter dan Implementasinya dengan Pengajaran Sastra - Nurweni Saptawuryandari (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2017)
This research is based on that lecture (short story) while it is not only reading book but it can be used for education. Short story SK Pensiun by Ahmad Tohari includes several education. This education means character education for example moral and behavior. We can divide until 2 items for solving this problem (1) how do they structure and they contains, (2) how do they representative character education, and (3) how character education lecture be can used for teaching lecture itself. This aims of this research is to know character education in this short story with uses analysis load structure. I use sintacys aspect, semantyc aspect and verbal aspect from Tzevton Todorov. From this way we can find items who describe education character. We also use describe analysis with collect input from libration. and the result from short story SK Pensiun is we can see education character example responsibility, respect, honour, helping each other, environmental responsibility, tolerance and do not lie.